Analisis Faktor-Faktor yang Mempengaruhi Kesejahteraan Perawat (Journal of Telenursing (JOTING), 2024)
This research aims to find out what factors influence the welfare of nurses in Bogor Regency. The research method used is correlational analysis with a cross sectional approach. The research results show that factors related to nurses' welfare are workload, training and development, team and management support, resources, recognition and appreciation and health care guarantees, involvement in decision making with a p-value